Apakah Keberadaan Komisaris Keluarga Dan Komisaris Independen Meningkatkan Pengungkapan Risiko? - Setiawan, Doddy; Andriyanto, Elisa Apriliani (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 14 No 1 (2019)DO - 10.24843/JIAB.2019.v14.i01.p01, 2019)
This research aims to examine the effect of family commissioners and independent commissioners on risk disclosure using Indonesian firms that engaged in initial public offering (IPO). This research uses multiple regression analysis to test the effect of family commissioners and independent commissioners on risk disclosure. The study sample consists of 204 non-financial firms that engaged in IPO during the period of 2001–2017. The result of the study shows that family commissioners and independent commissioners have positively affected risk disclosure. Therefore, it is important for companies to add more independent commissioners and maintain family commissioners during IPO. Keywords: family commissioners, independent commissioners, initial public offering, board of commissioner